Time to link camel genomics and traits by bridging the phenotypic gap - Almathen, Faisal; Salim, Bashir (Frontiers in Genetics, 2025)
Camels (Camelus dromedarius and Camelus bactrianus) are indispensable to the economy and culture of arid and semi-arid regions, providing milk, meat, transportation, and labor while demonstrating remarkable adaptations to extreme environments. Recent advances in camel genomics have unraveled key genetic insights related to diversity, physiological adaptation, and productivity traits. However, translating these genomic discoveries into practical applications remains limited by a critical gap in phenotypic data, standardized trait recording, and robust pedigree infrastructure essential foundations for implementing genomic selection (GS) effectively. The lack of high-density SNP arrays, variable linkage disequilibrium patterns, and incomplete genome assemblies further complicate efforts to identify causal variants, cautioning against overinterpreting GWAS results. This review provides a comprehensive analysis of camel genomics, emphasizing key genetic markers associated with growth, meat and milk production, coat color, athletic performance, environmental adaptation, cartilage integrity, and behavioral traits. Additionally, it highlights the importance of modeling genotype-by-environment interactions (G × E) and adopting advanced statistical approaches, such as random regression and reaction norm models, to capture complex trait architectures. Drawing lesson from other livestock, we propose a strategic roadmap that includes the development of high-density SNP arrays, improved genome assemblies, standardized trait recording, and establishment of large, connected training populations. International collaboration through a camel genomics consortium is essential to harmonize data, enhance genetic connectedness, and enable multi-environment evaluations. Addressing these research gaps will facilitate the development of precision breeding, climate-resilient livestock strategies, and sustainable conservation initiatives, ensuring that camels continue to thrive amid growing environmental and economic challenges.